Subaxial Cervical Spine Alignment After C1 to C2 Fusion. Issue 3 (August 2016) - Westwick, Harrison J.; Shamji, Mohammed F.
Abstract : Atlantoaxial fusion is a common strategy for managing segmental C1 to C2 spinal instability, with an incidence of postoperative subaxial instability (kyphosis and subaxial subluxation) of up to 40%. Our objective was to conduct a literature review of atlantoaxial fusion postoperative subaxial instability, addressing incidence, specific risk factors, and management. An online PubMed/MEDLINE and EMBASE search for subaxial deformity associated with atlantoaxial fusion was conducted. Sixteen research studies addressing atlantoaxial postoperative subaxial instability were identified. Subaxial kyphosis and subaxial subluxation were the primary cervical postoperative deformities identified, with incidences of each reported as high as in 40% of patients. A relationship between atlantoaxial fusion angle and C2 to C7 angulation was identified. Risk factors for such deformity include C1 to C2 fusion hyperlordosis, spontaneous subaxial vertebral fusion, rheumatoid arthritis, and selected fusion techniques. Management strategies including subaxial cervical fusion are discussed.